Economic comparisons of littoral production of low carbon fuel from non-fossil energy sources and seawater. (1st January 2018) - Willauer, Heather D.; Hardy, Dennis R.; Baldwin, Jeffrey W.; DiMascio, Felice; Williams, Frederick W.; Bradley, Matthew J.; Hoheisel, Raymond
Abstract: The remote military installation at Diego Garcia is used as an economic and strategic example of the many possible future naval or commercial sites and scenarios that could be utilized for the production of sustainable low carbon fuel from non-fossil electrical energy. In addition to photovoltaic (PV) and wind electrical sources, this analysis includes light water reactors (LWRs) on mobile platforms as the main electrical energy source. Using published capital cost estimates and a range of solar and wind renewable electrical energy scenarios, costs ranging between 6.40 and 12.57 per gallon of standard fuel are estimated for a 129, 000 gallons/day fuel process. The cost estimate for a floating nuclear electrical scenario is between 4.66 and 9.47 per gallon. Larger area potential sites of strategic naval and/or commercial importance such as Guam and Djibouti provide additional operational scenarios. Most importantly these military examples provide a framework for how such a process could be used commercially to supply stored energy as a sustainable fuel source for remote countries poor in fossil fuel resources. This information may also be used by policy analysts to support alternative energy implementation strategies and greatly expand the naval and commercial role in nuclear and renewable energy aimed at sustainable production of low carbon fuel. Highlights: An economic analysis for synthesizing fuel from non-fossil electrical energy is provided. Solar, wind, and floating nuclear electrical scenarios are used for synthesizing fuels. The analysis suggests that low carbon fuel could be synthesized between 4.66 to 12.57/gallon. The analysis provides one further step towards establishing sustainable full scale fuel synthesis processes.